Investigating Awareness of Pesticide Exposure as a Risk Factor for Parkinson’s Disease and Uptake of Exposure-Mitigating Behaviour in Farming Communities in Ireland - Lucy M. Collins; Éilis J. O’Reilly; Joan Omosefe Osayande; Fionnuala Wilson; Jolie Morisho; Rebekah Bevans; Rachel Roberts; Bereniece Riedewald; Louise M. Collins; Gerard W. O’Keeffe; Aideen M. Sullivan (Safety, 2025)
Parkinson’s disease (PD) is an age-related neurological disorder with increasing incidence and modifiable risk factors. People exposed to pesticides have up to a 2-fold higher risk of developing PD. Use of personal protective equipment (PPE) when using pesticides can lower an individual’s exposure. We examined awareness of the relationship between pesticides and PD risk in individuals working/living on farms in Ireland. We also investigated the practice of behaviours aimed at mitigating exposure, such as using PPE. An online survey was completed by a sample of the farming community (n = 707) attending agricultural fairs, and included demographics, lifetime/current residence/work on farms, pesticide contact, PPE use, PD diagnosis, and awareness of pesticide–PD association. Among participants, 51% worked/lived on farms and 62% reported contact with pesticides. Only 69% of those with pesticide contact reported using PPE, with gloves (57%) and masks (50%) most commonly used. Only 22% were aware of an association between PD and pesticides, and awareness did not increase PPE use. Among people with PD, only 40% had knowledge of the risk. We found that in a highly agricultural economy, occupational exposure to pesticides is common, but mitigation behaviours are not optimal. Educational campaigns to improve awareness of health risks from pesticides and to encourage PPE use could lower the personal and healthcare burden of PD and other health outcomes.